PERANCANGAN ALAT PENDETEKSI KADAR ALKOHOL DAN ASAP ROKOK PADA NAFAS MANUSIA - Muhammad Haris; I Made Budi Suksmadana; Syafarudin Ch. (DIELEKTRIKA, 2017)
Alcohol and carbon monoxide are very dangerous for human’s body. The effect of consuming alcohol can make us queasy and disfunction of our neural and brain. Them also happened when carbon monoxide was sniffed by our body, it also may cause heart attack etc. The censor to detect the content of alcohol is MQ-3, and MQ-2 is used to detect the content of CO. This research measures the content of alcohol by the BAC (Blood Alcohol Calculator) method while the smoke uses percentage of CO content. The instrument uses MQ-3 and MQ-2 censors with arduino control to get the data, then it will be transferred by bluetooth (HC-05) into smart phone to see the data’s from the censors. Appmitinvertor program is used in the smart phone. Result of measurement is the instrument can work to get the content of alcohol and smokes. The instrument is used equation of order 3 for the alcohol and equation of order 2 for the smokes (CO). Average error for the alcohol is 4,08% and 0,02% for the smokes.